2012
DOI: 10.1128/aem.05904-11
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Composition of Epiphytic Bacterial and Archaeal Ammonia Oxidizers of Marine Red and Brown Macroalgae

Abstract: Ammonia-oxidizing bacteria (AOB) and archaea (AOA) are important for nitrogen cycling in marine ecosystems. Little is known about the diversity and abundance of these organisms on the surface of marine macroalgae, despite the algae's potential importance to create surfaces and local oxygen-rich environments supporting ammonia oxidation at depths with low dissolved oxygen levels. We determined the abundance and composition of the epiphytic bacterial and archaeal ammonia-oxidizing communities on three species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 45 publications
1
23
2
Order By: Relevance
“…These findings are in contrast with our hypothesis and previous studies, in which the rhizosphere and root surfaces of freshwater macrophytes strongly favored the development of AOA over AOB (11,12). However, it was recently shown that macroalgal surfaces in marine systems harbor a higher abundance of AOB than AOA (33). This indicates that the presence of plants or specific plant species alone cannot account for the relative differences of one or the other group of ammonia oxidizers.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…These findings are in contrast with our hypothesis and previous studies, in which the rhizosphere and root surfaces of freshwater macrophytes strongly favored the development of AOA over AOB (11,12). However, it was recently shown that macroalgal surfaces in marine systems harbor a higher abundance of AOB than AOA (33). This indicates that the presence of plants or specific plant species alone cannot account for the relative differences of one or the other group of ammonia oxidizers.…”
contrasting
confidence: 56%
“…The 16S rRNA genes of Bacteria and Crenarchaeota and the amoA genes coding for the bacterial and archaeal ammonia mo-nooxygenases were quantified in sediment and rhizosphere samples as described previously (33,35). No relationship was found between amoA gene abundances and PNR when both root and sediment samples were considered together.…”
mentioning
confidence: 99%
“…Copy numbers of bacterial, crenarchaeal and thaumarchaeal 16 s rRNA gene were determined in DNA extracts from biofilm samples by qPCR using the conditions described in Trias and colleagues (). PCR efficiency ranged between 80% and 90% with r 2 values > 0.99.…”
Section: Methodsmentioning
confidence: 99%
“…Diverse bacteria live within the biofilm; however, these bacteria are not randomly distributed among different algal species. Each algal species hosts and supports bacterial communities with different species compositions, and the same algal species tends to host the same bacterial community, even in different environments (Lachnit et al ., 2009; Trias et al ., 2012). This phenomenon may occur because the host species may have markedly different spatial environments, physiological states, and chemical factors (including QS metabolites), which determine the composition of the associated bacterial community.…”
Section: Ecological Functions Of Qs During Algal-bacterial Interamentioning
confidence: 99%